Optimization of The Fermentation Process of Kimchi. (October 2019) - Sui, Ming; Qu, Peng; Zhu, Yusong; Zhang, Fengying; Li, Chunming
Abstract: This paper focuses on the effects of salt, sugar and temperature on the sensory evaluation of the product. The fermentation process is optimized by single factor experiment and orthogonal experiment. The results showed that salt, sugar and temperature had significant effects on the sensory score of naturally fermented kimchi. The optimum process parameters were: 3% of salt, 2% sugar, 30 °C fermentation temperature and 4 days fermentation time. The kimchi produced by this formula and process has the highest sensory score of 89.0 points. Under the best formula, kimchi has a strong aroma, moderate sweet and sour taste, and has the unique aroma of pickled kimchi. It has a rich aftertaste, good chewability and no roughness.